The green library planner what every librarian needs to know before starting to build or renovate - Carr, Mary M. 1950- (The Scarecrow Press, Inc., 2013)
Green buildings are better buildings. In fact, buildings use 36% of the energy in the United States, according to the Environmental Protection Agency, so green buildings that use less energy help to address the very real challenges of reliance on fossil fuel and climate change. More than only being environmentally responsible, green libraries are beautiful, cost-effective, high-performance buildings that enhance occupant health and comfort. This book is designed for members of library building design teams who typically are not actively engaged in architecture, construction, or engineering, but who need an introduction to the rationale for green buildings, the elements of green building, and the language of the field. It will be equally useful for public officials, boards, or administrators who are considering a new green library building, a renovated library structure, or sustainable elements for a current library facility.--(Source of description not identified)